(untitled) (Research, Society and Development, 2025)
The parathyroid glands play a crucial role in regulating calcium in the body through the secretion of parathyroid hormone (PTH). This study aimed to discuss the anatomical variations of these glands, their clinical and surgical implications, as well as the appropriate surgical treatments for related conditions, such as hyperparathyroidism. Methodology: A literature review was performed using descriptors such as “ectopic and topical parathyroids”, “ectopic parathyroid”, “anatomical variations of the parathyroid”, “hyperparathyroidism” and “parathyroidectomy” in databases such as the Virtual Health Library (BVS); National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), EbscoHost and Google Scholar. Results: Studies indicate that, although the typical location of the parathyroids is around the thyroid, approximately 15.9% of patients have ectopic glands, located in the neck or mediastinum. These variations may interfere with the efficacy of surgeries, such as parathyroidectomy, and with the maintenance of postoperative calcium homeostasis. Imaging tests, such as scintigraphy and ultrasound, are essential in surgical planning. Conclusion: It is concluded that detailed knowledge of the anatomy of the parathyroid glands is essential to avoid complications during surgery, such as nerve injuries or hypoparathyroidism.